2017
DOI: 10.3389/fpls.2016.02023
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis Reveals Extensive Light Stress-Response Reprogramming in the Seagrass Zostera muelleri (Alismatales, Zosteraceae) Metabolism

Abstract: Seagrasses are marine ecosystem engineers that are currently declining in abundance at an alarming rate due to both natural and anthropogenic disturbances in ecological niches. Despite reports on the morphological and physiological adaptations of seagrasses to extreme environments, little is known of the molecular mechanisms underlying photo-acclimation, and/or tolerance in these marine plants. This study applies the two-dimensional isoelectric focusing (2D-IEF) proteomics approach to identify photo-acclimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 59 publications
0
35
0
1
Order By: Relevance
“…LL plants had the lowest respirations rate (per unit biomass and per plant), suggesting that these plants reduced their metabolic rates to save energy. Proteonome analyses have demonstrated that prolonged exposure to shade induces a significant down‐regulation of key enzymes related to photosynthesis, carbohydrate metabolism, and amino acid synthesis in Zostera muelleri (Kumar et al ). Metabolomic studies on Z. marina support these findings: the quantities of sucrose, fructose, and most amino acids declined in plants exposed to shade for ca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LL plants had the lowest respirations rate (per unit biomass and per plant), suggesting that these plants reduced their metabolic rates to save energy. Proteonome analyses have demonstrated that prolonged exposure to shade induces a significant down‐regulation of key enzymes related to photosynthesis, carbohydrate metabolism, and amino acid synthesis in Zostera muelleri (Kumar et al ). Metabolomic studies on Z. marina support these findings: the quantities of sucrose, fructose, and most amino acids declined in plants exposed to shade for ca.…”
Section: Discussionmentioning
confidence: 99%
“…The response of seagrasses to multiple stressors has lately been addressed experimentally in a number of two-factor studies where potential interactions between a variety of factors have been addressed (Hootsmans et al 1987;Kahn and Durako 2006;Koch et al 2007;de los Santos et al 2010;Collier et al 2011;H€ offle et al 2011;Holmer et al 2011;La Nafie et al 2012;Jiang et al 2013;Villaz� an et al 2013;York et al 2013;Salo and Pedersen 2014;Castorani et al 2015;Villaz� an et al 2015;Hasler-Sheetal et al 2016;Moreno-Mar� ın et al 2016). The conclusions in many of these articles infer a prevalence of synergistic effects in seagrasses when exposed to multiple stressors, although this has rarely been tested explicitly.…”
mentioning
confidence: 99%
“…Protein (300 μg) was separated by isoelectric focusing (IEF) using a cup-loading method according to Kumar et al ( 2017 ). Immobilized pH gradient (IPG) strips (Bio-Rad, pH 3–10 or 5–8, 11 cm) were passively rehydrated in UTC7 rehydration solution for a minimum of 6 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Randomly selected protein spots were excised from gels, trypsin digested, and analyzed by LC/MS/MS according to Kumar et al ( 2017 ). Using an autosampler, connected to a nanoLC system (Tempo Eksigent, USA), 10 μL of the sample was loaded at 20 μL/min with MS loading solvent (2% Acetonitrile + 0.2% Trifluoroacetic Acid) onto a C8 trap column (CapTrap.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation